Dative versus electron-sharing bonding in the isoelectronic argon compounds ArR+ (R = CH3, NH2, OH, and F). (5th January 2021) - Liu, Zhiling; He, Jing; Li, Ya; Bai, Yan; Lin, Qingyang; Guo, Yurong; Zhang, Fuqiang; Wu, Haishun; Jia, Jianfeng
Abstract : For the series of isoelectronic ArR + (R = CH3, NH2, OH, and F) complexes, the nature of the bonding between Ar and R shifts from an Ar → R + dative σ bond in ArCH3 + and ArNH2 + to an Ar + –R electron-sharing σ bond in ArOH + and ArF + . Abstract : A computational investigation of the isoelectronic ArR + (R = CH3, NH2, OH, and F) species has been performed. The ground states of all four complexes are determined to be the lowest singlet isomers. A range of state-of-the-art quantum chemistry methods have been utilized to systematically examine the Ar–E bonds (E = C, N, O, and F) in these Ar-containing complexes, which could be categorized to be of covalent type with a gradual increase in the covalent character along C to F. Moreover, the nature of the Ar–E bond roughly depends on the ionization potential difference between the Ar atom and R radical, except for ArOH + . The dative Ar → R + bond is found for both ArCH3 + and ArNH2 + complexes, whereas the Ar–E bonds in both ArOH + and ArF + are better described as electron-sharing Ar + –R bonds.